Unusual case of appendicitis - Allen, L; Tsai, A (BMJ Publishing Group, 2016)
A teenage girl was admitted to the paediatric assessment unit with non-specific abdominal pain that gradually localised to the right iliac fossa (RIF). She remained systemically well; investigations including blood tests, urine sample and abdominal ultrasound were inconclusive. Surgical opinion was sought and the decision was made to perform a diagnostic laparoscopy due to the ongoing pain. Laparoscopy showed no evidence of any significant pathology, and appendicectomy was performed following the routine practice. Numerous pinworms came out while the appendix was resected. The RIF pain resolved and the patient made a full post-operative recovery. A stat dose of mebendazole and amoxicillin were given and the immediate family was also treated. Enterobius vermicularis (pinworm) causes significant morbidity worldwide and has a high prevalence among children in the UK. It can be easily treated and prompt recognition based on clinical symptoms can potentially prevent unnecessary surgery.